Human Resource Development in Birth Certificate Making Services at The Service of Population and Civil Registration of Kuningan District - Yanto Heryanto; Agus Dimyati; Wendy Rivansah (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
Human Resource Development is any effort to improve the implementation of current and future work, by providing information, influencing attitudes, or adding skills, in other words, development is any activity intended to change behavior consisting of knowledge, skills, and attitudes. One of the objectives of human resource development according to Hasibuan is to improve services. The focus of the research conducted by the author is on the service of making birth certificates. The method used is a qualitative research method which is a method for exploring and understanding the meaning that a number of individuals or groups of people ascribe to problems. The informant retrieval technique uses Purposive Sampling which is a sampling technique with certain considerations. This technique includes people who are selected on the basis of certain criteria that are considered capable of providing information in accordance with the focus of the research. The results of this study are based on the dimensions of the research that in terms of knowledge it is still said to be not optimal due to formal education that does not meet the criteria and also lack of participation in non-formal education. For the skill dimension, it is also still not optimal because there is no special training on making birth certificates. However, the attitude and behavior dimensions are optimal. The factors that become obstacles are the rapid development of technology and the lack of discipline of employees. In addition, the efforts made are to carry out direction, supervision, and as well as sharing knowledge between fellow employees